2019
DOI: 10.1002/pola.29325
|View full text |Cite
|
Sign up to set email alerts
|

Direct Heteroarylation versus Stille Polycondensation Reaction for the Synthesis of TQ1 Conjugated Polymer

Abstract: We report a facile synthesis of the well‐known and highly promising conjugated polymer TQ1 using eco‐friendly direct heteroarylation reaction. Optimization of the reaction conditions yielded the target polymer with good optoelectronic and charge‐transport characteristics. The TQ1 polymer obtained in the direct heteroarylation reaction delivered power conversion efficiency of ∼5% in organic bulk heterojunction solar cells, which matches well the characteristics of the reference devices assembled using TQ1 batch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…An increasing number of studies have compared the optical and electronic properties of polymers made using the DARP method versus those made using the Stille reaction, and have shown that similar properties can be achieved. 122,[125][126][127][128][129][130] In this article, we will delve into a comprehensive comparison between the Stille reaction and the DARP method.…”
Section: Alternatives To Stille Polycondensationmentioning
confidence: 99%
“…An increasing number of studies have compared the optical and electronic properties of polymers made using the DARP method versus those made using the Stille reaction, and have shown that similar properties can be achieved. 122,[125][126][127][128][129][130] In this article, we will delve into a comprehensive comparison between the Stille reaction and the DARP method.…”
Section: Alternatives To Stille Polycondensationmentioning
confidence: 99%
“…Furthermore, Troshin et al 79 reported the synthesis of the low-cost material TQ1 (see Figure 2) by DHAP and compared its properties with the Stille-based polymer. After careful reaction optimizations, the authors were able to obtain a M n of about 30−33 kg mol −1 for both DHAP and Stille reactions.…”
Section: Toward Sustainable Opvsmentioning
confidence: 99%
“… 1 , 2 , 12 , 14 19 ) are ubiquitous in all kinds of synthetic conjugated polymers and have prompted intensive studies of structure-function relationships in organic electronics 2 , 14 16 , 20 , 21 . In particular, taking advantage of the widespread application of palladium-catalyzed polycondensations (including Stille coupling or Suzuki-Miyaura coupling) 1 , 22 , 23 , much efforts have been devoted to developing DP-insensitive polymer donor ( P D ) and polymer acceptor ( P A ) materials in PSCs 24 26 . However, the aromaticity and reactivity of conjugated polymers undergo variations with the chain length and pre-aggregation among the living polymer chains during chain-growth polymerization.…”
Section: Introductionmentioning
confidence: 99%